Trends in pelvic organ prolapse management in Latin America. Issue 3 (6th September 2017) - Plata, Mauricio; Bravo‐Balado, Alejandra; Robledo, Daniela; Castaño, Juan C.; Averbeck, Márcio A.; Plata, Manuel A.; Cataño, Juan G.; Caicedo, Juan I.; Trujillo, Carlos G.
Abstract : Aims: To describe practice patterns and perspectives regarding pelvic organ prolapse (POP) management among urologists, gynecologists, and urogynecologists in Latin America (LATAM). Methods: A cross‐sectional study was conducted from April to September 2016 using a 37‐item internet‐based survey applied to members of urologic and gynecologic associations from 18 countries. Participants were asked about their background and practice patterns. Descriptive statistics were employed. Results: A total of 673 responses were obtained. Most came from Colombia (33.6%) and Brazil (24.7%). The number of practitioners who perform at least one POP procedure per month and were eligible to finish the survey was 529 (78.6%), out of which 323 (61.0%) were urologists, 156 (29.5%) gynecologists, and 50 (9.5%) urogynecologists. Mesh‐based POP repairs were used by 57.1% of participants. Out of non‐mesh users, the most frequent vaginal procedures were sacrospinous fixation (30%), colporrhaphy (25%), and uterosacral fixation (12%). Regarding the impact of FDA warnings, 75.2% participants indicated that the use of mesh has declined, and 41.9% considered this has had a negative effect in the use of incontinence tapes as well. Only two physicians reported legal disputes related to mesh procedures, and 75.8% said they would still indicate mesh repairs in certain cases. Conclusions: This is the first report on POP practice patterns in LATAM. Preferences regarding surgical management of POP are not very different from international trends. Despite intense scrutiny and media exposure, mesh‐based procedures are still largely used in LATAM.